Удосконалення адміністративно-правового регулювання кадрового забезпечення Державного бюро розслідувань як важлива умова ефективної реалізації правоохоронної функції держави - Салманова, О. Ю.; Salmanova, O. Yu.; Olena Salmanova (Право.ua. - 2023. - № 4. - С. 57-62, 2023)
Встановлено та надано юридичний аналіз системоутворюючих елементів кадрового забезпечення Державного бюро розслідувань, визначено їх особливості та виявлено проблемні аспекти реалізації в практичній діяльності.

The article examines the current aspects of the administrative and legal regulation of personnel support of the State Bureau of Investigation. It was emphasized that the importance of the problem of administrative and legal regulation of staffi ng of the State Bureau of Investigation is based on the dynamics of the processes of introducing a complex of reforms and transformations in the domestic law enforcement sphere. It was noted that the development of the newest system of law enforcement bodies, represented by the SBI, is a consequence of the urgent demand of society to eradicate corruption in the system of public administration bodies. It was determined that the complex and coordinated process of staffi ng of law enforcement agencies of the state is fully refl ected in practical activities in the ways, order, forms and procedures provided for by the current administrative legislation. It has been established that to date in the scientifi c legal literature there is a lack of a single approach to the use by scientists of the defi nitions of “personnel”. It is emphasized that the defi nition of “personnel” in the public service is considered by administrative scientists in a broad and narrow sense. From a broad perspective, personnel are interpreted as a circle of offi cials whose main task is the development and implementation of decisions in the fi eld of public administration. From a narrow point of view, personnel are exclusively a collection of offi cials. It was emphasized that it is proposed to consider the personnel of the public service as an element of the state personnel.

Предоставлен юридический анализ системообразующих элементов кадрового обеспечения Государственного бюро расследований, определены их особенности и выявлены проблемные аспекты реализации в практической деятельности.
Keywords: адміністративно-правове регулювання; Державне бюро розслідувань; кадрове забезпечення; персонал; особовий склад; правоохоронна функція; професіоналізм; administrative and legal regulation; State Bureau of Investigation; human resources; personnel; law enforcement function; professionalism; административно-правовое регулирование; Государственное бюро расследований; кадровое обеспечение; персонал; личный состав; правоохранительная функция; профессионализм